2009
DOI: 10.1158/1541-7786.mcr-08-0263
|View full text |Cite
|
Sign up to set email alerts
|

Antifolate Activity of Pyrimethamine Enhances Temozolomide-Induced Cytotoxicity in Melanoma Cells

Abstract: Most metastatic melanoma patients fail to respond to available therapy, underscoring the need to develop more effective treatments. We screened 2,000 compounds from the Spectrum Library in human melanoma cell lines to identify compounds that enhanced the cytotoxic effect of temozolomide, a drug used to treat metastatic melanoma. Screening was done with the temozolomide-resistant melanoma cell line SK-MEL-19, and six compounds were identified that had little or no inherent cytotoxicity but significantly enhance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 44 publications
(47 reference statements)
4
31
0
3
Order By: Relevance
“…Parallel analyses were carried out in cells treated with Pyr and the chemotherapeutic agent TMZ at a clinically relevant concentration (100 μmol/L) [30]. We tested Pyr-analogues using the same dosage of Pyr (8 μg/ml), which is known to induce cell death in melanoma cells [10, 11] at different time points, i.e. after 24, 48 and 72 h of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel analyses were carried out in cells treated with Pyr and the chemotherapeutic agent TMZ at a clinically relevant concentration (100 μmol/L) [30]. We tested Pyr-analogues using the same dosage of Pyr (8 μg/ml), which is known to induce cell death in melanoma cells [10, 11] at different time points, i.e. after 24, 48 and 72 h of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also demonstrated that Pyr is a potent pro-apoptotic inducer in cancer cells, e.g. in metastatic melanoma cells [10, 11]. It has been suggested that the mechanism underlying this activity involves both the activation of the caspase cascade (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, at more ''clinically relevant'' concentrations no appreciable effect on cell cycle, proliferation, or temozolomide-induced DNA damage has been observed following temozolomide treatment in human melanoma cell lines (Chen et al, 2009), which may not be surprising as this agent has a low response rate in the clinic (Rietschel et al, 2008). Several studies have suggested that methyl-guanine methyl transferase and RR may be involved in the temozolomide-resistance mechanism in cancer (Aghi et al, 2006;Augustine et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has described the activation of NF-κB by the mitogen-activated protein kinase (MAPK) pathway in human melanoma cells (10). To investigate whether alterations in the MAPK pathway are also involved in the mechanism of CEL/TMZ-induced cytotoxicity, we examined the effect of TMZ/CEL treatment on expression levels of key molecules in the MAPK pathway.…”
Section: Involvement Of Mitogen-activated Protein Kinases In Tmz/cel-mentioning
confidence: 99%
“…In an effort to reduce these costs, we have performed screens of chemical libraries consisting of marketed drugs and natural compounds with the goal of identifying agents with antitumor effects that can be expedited to clinical trials. We recently identified a group of antifolates that enhance the cytotoxicity of TMZ in melanoma cells (10). The use of antifolates is limited in some patients, however, due to intolerable side effects, thus there is a need to identify alternatives.…”
Section: Introductionmentioning
confidence: 99%